Vector control complements mass drug administration against bancroftian filariasis in Tirukoilur, India - IP Sunish; R Rajendran; TR Mani; A Munirathinam; AP Dash; BK Tyagi (The World Health Organization, 2007)
OBJECTIVE: To determine the role of vector control in further decreasing the transmission of bancroftian filariasis achieved by mass drug administration and the long-term impact on filariometric indices. METHODS: Three rounds of annual mass drug administration, with diethylcarbamazine and ivermectin, were complemented by vector control (mainly using polystyrene beads) in villages of Tirukoilur, south India, during 1995-99. Subsequently, drug administration is being carried out with diethylcarbamazine and albendazole or diethylcarbamazine alone. We evaluated the impact of mass drug administration used alone or in conjunction with vector control (from 1995 to 2005) on vector transmission indices (such as transmission intensity index, monthly biting rate, monthly transmission potential and annual transmission potential). We analysed data on filarial infection in the community to estimate the prevalence of microfilaraemia and antigenaemia using chi2 analysis and Fisher's exact test. FINDINGS: Vector density greatly decreased in villages where vector control was used as an adjunct to mass drug administration and almost no infective mosquitoes were found in the small numbers still remaining. Filarial antigenaemia was low and continued to decrease significantly in the age group 15-25 years in villages receiving mass drug administration with vector control in contrast to villages receiving only mass drug administration. CONCLUSION: The gains of mass drug administration were sustained only with the integration of vector control measures. We advocate the incorporation of vector control in the Global Programme to Eliminate Lymphatic Filariasis as it can potentially decrease the time required for eliminating lymphatic filariasis.